Clinical and diagnostic aspects of Fabry disease management: a narrative review with a particular focus on Brazilian experts’ perspectives - Giugliani, Roberto; Marques, Sandra; Andrade, Luis G. M. De [UNESP]; Pessoa, André; Vaisbich, Maria H.; Blum, Angélica; Tenório, Fernanda; Rosa, Nilton S (Latin American Society Inborn Errors and Neonatal Screening (SLEIMPN); Instituto Genética para Todos (IGPT), 2022)
Research on the genetics, epidemiology, and clinical manifestations of Fabry disease (FD) has increased significantly in recent years. However, some relevant clinical questions still need to be answered to develop better approaches to patient management. This review focuses on answering specific questions raised by Brazilian experts based on their experience in diagnosing and managing patients with FD. The questions are as follows: What is the role of globotriaosylsphingosine in diagnosis? How does one proceed with the diagnosis if there is a variant of unknown significance? What are the earliest and most reliable markers of renal, cardiac, and neurological impairment? What is the prevalence of FD in patients with cryptogenic stroke? What is the average delay in diagnosis in patients with FD? Based on these questions, our objective was to highlight epidemiological, diagnostic, and clinical aspects relating to the literature in the FD field.
Keywords: Fabry disease; rare disease; diagnostic.